Photocatalytic hydrogen production using ethanol as sacrificial agent from gas and liquid phases on reduced graphene oxide-TiO2- Pt nanocomposites - Esteves, M. Alexandra (2020)
ABSTRACT: Various strategies such as heterostructuring, crystal/textural modifications and band gap engineering, have been applied to the improvement of the photocatalytic activity of Titania for hydrogen production from water splitting. In this work deposited Pt on TiO2 is used as electron trap to suppress charge recombination. To reinforce this effect, composites with graphene oxide (GO) have been prepared, exhibiting promising photocatalytic performance for both hydrogen generation and the degradation of ethanol added as hole scavenger. Photocatalytic reactions were conducted in gas and liquid phases.